Constrained firms, not subsistence activities: Evidence on capital returns and accumulation in Peruvian microenterprises - Kristin Göbel; Michael Grimm; Jann Lay (Institute for the Study of Labor (IZA), 2012)
We investigate the returns to capital and capital accumulation using panel data of Peruvian micro enterprises (MEs). Marginal returns to capital are found to be very high at low levels of capital, but rapidly decreasing at higher levels. The dynamic analyses of capital accumulation in MEs suggest that credit constraints explain a major part of the variation in firm growth. We find a very large positive effect of household non-business wealth on capital stocks of MEs. We also show a sizable effect of risk on accumulation and pronounced interactions between wealth and risk. The presented evidence is consistent with poorly endowed entrepreneurs who operate in imperfect capital markets and a very risky environment.
Keywords: D13; D61; O12; 330; micro and small enterprises; credit constraints; risk; risk aversion; firm growth; Peru; Kleinstunternehmen; Kapitalertrag; Investition; Verschuldungsrestriktion; Risikoaversion; Unternehmenswachstum; Peru